Release behavior and toxicity profiles towards leukemia (WEHI-3B) cell lines 6-mercaptopurine-PEG-coated magnetite nanoparticles delivery systems - Dorniani, Dena; Kura, Aminu Umar; Hussein-Al-Ali, Samer Hasan; Hussein, Mohd Zobir; Fakurazi, Sharida; Shaari, Abdul Halim; Ahmad, Zalinah (Hindawi Publishing Corporation, 2014)
The coating of an active drug, 6-mercaptopurine, into the iron oxide nanoparticles-polyethylene glycol (FNPs-PEG) in order to form a new nanocomposite, FPEGMP-2, was accomplished using coprecipitation technique. The resulting nanosized with a narrow size distribution magnetic polymeric particles show the superparamagnetic properties with 38.6 emu/g saturation magnetization at room temperature. Fourier transform infrared spectroscopy and the thermal analysis study supported the formation of the nanocomposite and the enhancement of thermal stability in the resulting nanocomposite comparing with its counterpart in free state. The loading of 6-mercaptopurine (MP) in the FPEGMP-2 nanocomposite was estimated to be about 5.6% and the kinetic experimental data properly correlated with the pseudo-second order model. Also, the release of MP from the FPEGMP-2 nanocomposite shows the sustained release manner which is remarkably lower in phosphate buffered solution at pH 7.4 than pH 4.8, due to different release mechanism. The maximum percentage release of MP from the nanocomposite reached about 60% and 97% within about 92 and 74 hours when exposed to pH 7.4 and 4.8, respectively.